2017
DOI: 10.1016/j.cell.2017.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Cells Mediate a Systemic RNAi-Based Adaptive Antiviral Response in Drosophila

Abstract: Effective antiviral protection in multicellular organisms relies on both cell autonomous and systemic immunity. Systemic immunity mediates the spread of antiviral signals from infection sites to distant uninfected tissues. In arthropods, RNA interference (RNAi) is responsible for antiviral defense. Here we show that flies have a sophisticated systemic RNAi-based immunity mediated by macrophage-like haemocytes. Haemocytes take up dsRNA from infected cells and, through endogenous transposon reverse transcriptase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
248
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(253 citation statements)
references
References 39 publications
2
248
0
3
Order By: Relevance
“…Experiments utilizing a reverse transcriptase inhibitor demonstrated that viral RNA is converted into vDNA by endogenous reverse transcriptase which is then used as a template to synthesize siRNAs for immune priming (Table S7). This group used a recently developed sequencing technique that can distinguish primary and secondary siRNAs to show that viral RNA is transcribed into DNA inside hemocytes in an Ago2‐dependent manner, and the DNA is then used as a template to synthesize secondary siRNAs de novo . This is the first time the existence of an RNAi amplification mechanism has been observed in insects .…”
Section: Potential Mechanisms Affecting Rnai Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments utilizing a reverse transcriptase inhibitor demonstrated that viral RNA is converted into vDNA by endogenous reverse transcriptase which is then used as a template to synthesize siRNAs for immune priming (Table S7). This group used a recently developed sequencing technique that can distinguish primary and secondary siRNAs to show that viral RNA is transcribed into DNA inside hemocytes in an Ago2‐dependent manner, and the DNA is then used as a template to synthesize secondary siRNAs de novo . This is the first time the existence of an RNAi amplification mechanism has been observed in insects .…”
Section: Potential Mechanisms Affecting Rnai Efficiencymentioning
confidence: 99%
“… This group used a recently developed sequencing technique that can distinguish primary and secondary siRNAs to show that viral RNA is transcribed into DNA inside hemocytes in an Ago2‐dependent manner, and the DNA is then used as a template to synthesize secondary siRNAs de novo . This is the first time the existence of an RNAi amplification mechanism has been observed in insects . The caveat is that this amplification mechanism is stimulated only in response to viral infections, and in the absence of a viral infection, exogenous dsRNA is converted only into primary siRNA, not into secondary siRNAs .…”
Section: Potential Mechanisms Affecting Rnai Efficiencymentioning
confidence: 99%
“…The importance of RNAi is most clearly illustrated by the specific generation of a siRNA pathway in somatic tissues of insects that is dedicated to defense against invading nucleic acids, and that is maintained separately from the miRNA pathway that regulates physiological and developmental processes [12,15]. The requirement for base-pairing prior to initiation of degradation provides great specificity and mechanisms for enhancement of efficiency have also evolved such as amplification via DNA forms and production of secondary siRNAs followed by systemic spread via exosomes [74,75]. On the other hand, efficiency of antiviral RNAi can be affected by physiological conditions such as nutritional status and stress [19,168].…”
Section: Resultsmentioning
confidence: 99%
“…Hemocytes are not efficiently infected with SINV, but are proposed to acquire viral dsRNA through phagocytosis of dying cells from other tissues [28] or direct endocytosis from the hemolymph. Uptake of dsRNA in combination with viral infection subsequently initiates an amplification mechanism in the hemocytes that comprises the generation of viral DNA forms (after reverse transcription by endogenous retrotransposons; [74]) that function as templates for the production of secondary viral siRNAs as an amplification mechanism [75]. Secondary viral siRNAs provide systemic protection after their secretion in exosomal-like vesicles that are formed from multivesicular bodies.…”
Section: Systemic Antiviral Rnai-based Immunitymentioning
confidence: 99%
“…More recently, Drosophila phagocytes were shown to capture viral RNA to produce and secrete short interfering RNA for the RNA interference of viral genomes or transcripts. 68) This mechanism explains the occurrence of anti-viral RNA interference in cells that are not infected with a virus. The production of virus-specific short interfering RNA appeared to last for a long time, and, thus, was regarded as immunological memory resembling the production of antibodies in evolutionarily higher organisms.…”
Section: Role In Phagocyte Priming Previous Studiesmentioning
confidence: 99%